The Influence of Perceived Value And E-Service Quality on Customer Satisfaction Among Users of the Soco By Sociolla Application in Surabaya - Siwi, Aurizka Fadia; Dermawan, Rizky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In the era of digital development, beauty, and personal care e-commerce has gained significant popularity among the public. SOCO by Sociolla is one of the beauty e-commerce platforms in Indonesia. The purpose of this research is to investigate the connection between perceived value and e-service quality and customer satisfaction among users of the SOCO by Sociolla application in Surabaya. The quantitive method is employed in this research. The population of this study is the people of Surabaya. The sample of this research was selected using purposive sampling to select individuals who met specific criteria. These criteria included downloading the SOCO by Sociolla application, actively using it by making purchases, and having a history of at least two separate purchases. Ultimately, the study included 91 respondents who met these criteria. The research utilized Smart PLS software as the analysis tool. This study’s conclusions demonstrate that among Surabaya City users of the SOCO by Sociolla, perceived value and e-service quality have a positive significant influence on customer satisfaction.